Is environmental enrichment effective in modulating autophagy markers in the brain exposed to adverse conditions? A systematic review - Silva, Clarice Beatriz Gonçalves; de Sousa Fernandes, Matheus Santos; Cerqueira, Debora Dantas Nucci; Santos, Gabriela Carvalho Jurema; Yagin, Fatma Hilal; Aygun, Yalin; Badicu, Georgian; Evangelista, Fabiana S.; Prieto-González, Pablo; Souto, Fabrício Oliveira; Dutta, Ashit Kumar; Al-Mhanna, Sameer Badri; et al. (Frontiers in Cellular Neuroscience, 2025)
Autophagy is a key regulator of cellular homeostasis and neuronal survival, particularly under adverse physiological conditions. Environmental enrichment (EE), a non-pharmacological intervention providing enhanced sensory, cognitive, and motor stimulation, may modulate autophagic processes in the brain. This systematic review aimed to synthesize preclinical findings on the effects of EE on autophagy markers in rodent models subjected to diverse adverse conditions. A literature search across PubMed, Scopus, ScienceDirect, and embase yielded eight eligible studies meeting inclusion criteria. EE was found to be generally associated with upregulation of key autophagic markers such as Beclin-1, LC3-II/LC3-I ratio, cathepsins, p62, p-TFEB, and LAMP-1 across brain regions including the cortex, hippocampus, and penumbral area. However, reductions in some markers were also observed, indicating that the modulatory effects of EE are context-dependent and may vary with disease model, brain region, or EE protocol duration. These findings suggest that EE holds promise as an adjunctive strategy to modulate autophagy and mitigate neurodegeneration, though heterogeneity in study design and outcomes warrants caution during interpretation. Further mechanistic and sex-specific studies are needed to clarify the therapeutic relevance of EE-induced autophagic modulation.